2014
DOI: 10.1007/s00420-014-0993-y
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei and chromosome aberrations in subjects occupationally exposed to antineoplastic drugs: a multicentric approach

Abstract: Because both MN and CA have been described as being predictive of group-increased cancer risk, our findings point to a need for improving specific safety procedures in handling and administering ANPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 62 publications
4
22
0
3
Order By: Relevance
“…Occupational exposure to antineoplastic agents has been recognized as a potential health hazard since the 1970s, when Falck et al ( showed an association between contact with antineoplastic drugs and increased urinary mutagenicity. Since then, a number of other studies have reported the toxic effects of anti‐cancer drugs on workers around the world (Villarini et al , ; Moretti et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposure to antineoplastic agents has been recognized as a potential health hazard since the 1970s, when Falck et al ( showed an association between contact with antineoplastic drugs and increased urinary mutagenicity. Since then, a number of other studies have reported the toxic effects of anti‐cancer drugs on workers around the world (Villarini et al , ; Moretti et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…We also have to draw attention to the widespread contamination of the patient toilet before and after drug handling started, as it puts family members at risk of exposure, making this a public health issue as well. These findings raise particular concern, because Moretti et al (13) showed in a recent study that handling cytotoxic drugs, even under controlled conditions, involves a considerable genotoxic risk (13).…”
Section: Figure 4 5-fu Contamination (Ng CM -2 ) Before and After Drumentioning
confidence: 99%
“…Even exposure to doses lower than those received by cancer patients can produce adverse health effects, especially in chronically exposed healthcare workers (13)(14)(15)(16). There have been reports of reproductive toxicity that can result in miscarriage, temporary or permanent infertility, preterm births, congenital malformations, and learning disabilities in the children of the exposed individuals (17,18).…”
mentioning
confidence: 99%
“…Numerous seminal studies have shown that exposure to antineoplastic medications can result in serious reproductive side effects, such as menstrual abnormalities, infertility, spontaneous abortions, and learning disabilities in the offspring of health care workers who have been exposed . More recent research also has shown that repeated exposure can result in DNA mutations and secondary malignancies . Although it may seem counterintuitive that medications used to treat cancer can also be oncogenic, disruption of DNA is the most common mechanism of action for antineoplastic chemotherapy, which can lead to mutations in healthy cells and result in clonal abnormalities and eventual cancer development…”
Section: Risks Associated With Hd Exposurementioning
confidence: 99%